The impact of the implementation of international financial reporting standards on the financial statements of Saudi listed companies: An empirical study on the Saudi German Health Company and SAPTCO - Al-Masoudi, Abduallah Hussein; Baqader, Saleh Muhammed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to identify the impact of the application of International Financial Reporting Standards (IFRS) on the financial statements of two Saudi companies listed in the Saudi stock market, Tadawul, namely the Saudi German Health Company and SAPTCO Company, from 2016 to 2018. The IFRS were applied to Saudi companies in 2017. In order to achieve the objectives of the study, reach the desired goals, and to be fully aware of the aspects of the research, the descriptive approach was used to list the facts related to the financial statements, and IFRS through the use of scientific sources related to accounting information, the use of financial ratios (return on assets and return on equity) and an application indicator Standards. The programs used to study and analyze the financial statements of the two study sample companies were SPSS and Microsoft Excel. That is through the correlation coefficients and the rate of change, where the financial data of the two study sample companies were collected. This included the statement of financial position and the income statement to achieve the relationship before applying the IFRS in 2016 and during the year of implementation (2017), and a year after the implementation (2018). The results showed that the IFRS had an impact on both companies which was reflected in their financial statements. This was also indicated by the financial ratios, correlation coefficient and regression coefficient. With regard to the financial ratios, the researchers found that the Saudi German Health Company achieved a higher return on assets, return on equity, and earning per share in all three years than those achieved by SAPTCO. The study recommends that companies listed in the Saudi stock market (Tadawul) should adhere to the application of IFRS, as this had a positive impact on the financial statements of the two sample companies.
Keywords: financial statements; international financial reports; application of international financial reporting standards; financial statements of Saudi companies